تقييم دور هيئات الإشراف في تطبيق قواعد الحوكمة من وجهة نظر العاملين في شركات التأمين "دراسة ميدانية على شركات التأمين العاملة في سورية" - زاهر بسام; بركات يسيرة; بركات حيان محمد (Latakia University Journal - Economic and Legal Sciences Series, 2013)
يهدف البحث إلى تسليط الضوء على الدّور الذي تقوم به هيئات الإشراف على شركات التأمين في تطبيق قواعد الحوكمة والالتزام بها, من ناحية إصدار التشريعات والقرارات الضروريّة لتطبيق الحوكمة, أو الرقابة على مدى تطبيق شركات التأمين لقواعد الحوكمة. تمّ في الدراسة استخدام المنهج الوصفي التحليلي من خلال استعراض مفهوم الحوكمة والأطراف المعنيّة بتطبيقها وتحديد طبيعة الجهات المشرفة على شركات التأمين, كما تمّت الدراسة الميدانيّة على سبع من شركات التأمين الخاصة في سورية, ومن أجل تحقيق أهداف الدّراسة تمّ توزيع استبيان, ومن ثمّ تحليل الإجابات الواردة باستخدام البرنامج الإحصائي SPSS. خلُصت الدّراسة إلى أنّ هناك دورا جيّدا تقوم به هذه الهيئات في إلزام شركات التأمين وتشجيعها لتطبيق الحوكمة سواء كان ذلك من الناحية التنظيمية والتشريعية أو الرقابية. دعت الدراسة الجهات كافة إلى توحيد جهودها في مجال تطبيق الحوكمة من خلال إصدار المبادئ والقرارات الخاصة بالحوكمة, وكذلك التقارير المرتبطة بتطبيقها, وإجراء الدورات التدريبية وإقامة الندوات الخاصة بالحوكمة, وذلك بهدف تعزيز دور الهيئات في تطبيق الحوكمة بما ينعكس إيجابا على الشركات. الكلمات المفتاحيّة: حوكمة الشركات, التأمين, الرقابة, هيئة الأوراق والأسواق المالية السورية, هيئة الإشراف على التأمين في سورية. The research aims to shed light on the role played by the bodies overseeing the insurance companies in applying the rules of governance and abiding them in terms of issuing legislations and resolutions necessary to implement governance, or control over the application of insurance companies to governance rules. In this study, the descriptive analytical approach was used by reviewing the concept of governance and the parties concerned to apply it, and identifying the nature of the supervisor of insurance companies. The study took place in seven of the private insurance companies in Syria. A questionnaire has been distributed to achieve the goals of this study and analyzed the received answers using the statistical techniques by SPSS. The study concluded that there is a good role played by these bodies in binding and encouraging insurance companies to implement corporate governance, whether it is in terms of regulatory and legislative or supervisory sides. The study called for all parties to unite their efforts in the field of application of Corporate Governance, whether it’s through the issuance of principles and decisions related to the subject of governance or issuing reports that are associated with implementing insurance companies for Corporate Governance and holding training courses and seminars on the subject of governance in order to enhance the role of these bodies in the application of governance and consequently reflecting positively on the work of companies.